PENGGUNAAN METODE SNOWBALL THROWING DALAM MENINGKATKAN HASIL BELAJAR IPS KELAS V SDN 007 PURNAMA KECAMATAN DUMAI BARAT KOTA DUMAI - Rosidawati (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2016)
The low value of students is caused by the wrong way teachers teach. Students tend to get bored in the subjects at school because teachers dominate the learning process. This results in students feeling compelled to follow the lessons. This study aims to improve student learning outcomes in social studies class V SDN 007 Purnama Kota Dumai. The study was conducted from January 4 to January 12, 2012, involving 26 students of class V, consisting of 15 male and 11 female students. This research consisted of two cycles, each cycle comprising two meetings. To obtain data on student learning outcomes in the implementation of learning using the throwing snowball method, a written test was used. Meanwhile, to assess teacher and student activities, observation sheets were utilized. The results of the study showed that student activity in the first cycle at meeting I reached only 45.1% (poor category), while in meeting II it increased to 59.2% but still remained in the poor category. In the second cycle, student activity at meeting I increased to 68.7% (still in the poor category), and in meeting II rose significantly to 86.9% (good category). Learning outcomes in the first cycle at meeting I reached a total score of 1280 with an average of 50 (poor category). In meeting II of the first cycle, learning outcomes increased to 1850 with an average score of 71.15 (fair category). In the second cycle, learning outcomes at meeting I reached 2095 with an average of 80.3 (good category). In meeting II, the score rose to 2116 with an average of 81.38 (good category). Thus, it can be concluded that the throwing snowball learning model can improve student learning outcomes in social studies learning for class V at SDN 007 Purnama Kota Dumai.